Budi Daya Selada Hidroponik dengan Instalasi DFT dan Pompa Air Tenaga Surya pada UMKM Tani “Aneka Jaya" Kelurahan Lalolang, Kecamatan Tanete Rilau, Kabupaten Barru - Rosdiana, Rosdiana; Mahmud, Usamah; AZ, Wahyul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program was conducted as an effort to empower target groups through the implementation of technological innovations relevant to local needs. The approach included training, mentoring, and direct application of technology, enabling the community to acquire practical and sustainable skills. The program focused not only on enhancing individual capacity but also on strengthening group institutions to become more independent and capable of developing local potential. The results indicated an increase in knowledge, skills, and motivation among community members in managing their resources and enterprises. Furthermore, the program created an effective collaboration model between universities, local government, and community groups. Therefore, this initiative is expected to provide a tangible contribution to sustainable development based on active community participation.